Comparative analysis of immune markers in multiple sclerosis and rheumatoid arthritis patients with oral disease - Esra Hassan Abd Ali; Suzan Mohammed Abdul Raheem; Hussain Owaid Muhammed; Alzahraa Jubbar Jassim; Abdullah Jasem (Folia Medica)
Introduction: A substantial body of research has underscored the intricate nature of diagnosing oral disorders in conjunction with chronic inflammatory diseases. Aim: Multiple sclerosis (MS) and rheumatoid arthritis (RA) are chronic autoimmune diseases, which are usually difficult to distinguish in the early stage of the diseases. The objective of this study was to explore the differences of immune mechanism and diagnostic markers through bioinformatics analysis of the pro-inflammatory cytokine’s markers (IL-1β, IL-6, and TNF-α) to evaluate the role of immunological markers in patients with MS and RA with oral diseases. Materials and methods: This study enrolled 54 patients with oral disorders and chronic inflammatory diseases admitted to our hospital between January 2020 and December 2022, among 587 patients who had MS or RA and 50 healthy controls without oral disorders, with age, sex, and familial and genetic factors matching. Oral disorders were diagnosed and staged according to the method of dental examination. Blood (IL-1β, IL-6, and TNF-α) levels were measured using ELISA to detect chronic inflammatory diseases. Results: Important changes were found in RA and MS patients in terms of their age at onset of disease: RA patients exhibited a higher average age of onset (47.29 years) compared to MS patients (30.56 years), with both conditions showing a female predominance. Genetic factors did not differ significantly between the two conditions. Patients with both chronic inflammatory diseases and oral disorders had elevated levels of the studied markers (IL-1β, IL-6, and TNF-α) compared to those without oral disorders, indicating a substantial impact of oral diseases on immunological responses. Conclusions: RA typically affects older individuals, while MS onset occurs at a younger age with a higher female prevalence. Xerostomia was more common in RA, while oral candidiasis was more common in MS. Both active MS and patients with oral disorders exhibit high concentrations of IL-1β, IL-6, and TNF-α markers. These outcomes may have inferences for understanding the immune reaction and inflammation in these conditions.